The Prevalence of Gall Stones in Acute Pancreatitis A Prospective View from Lady Reading Hospital MTI Peshawar KP - Naeem Mumtaz, Attaullah Arif, Syed Nadeem Ali Shah, Almas Samo, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To see the prevalence of gall stones in patients admitted at a tertiary care center with acute pancreatitis. Methods: This is a single center based observational cross sectional study carried out from February 2022 to July 2022 on a sample of patients at casualty surgical bay and general surgical department of tertiary care hospital located in KP province of Results: Total 106 patients were included in this study. Females 69.8% outnumbered males 30.2% with Mean SD 1.70 ± 0.461. Out of all patients admitted with acute pancreatitis 64.2% found to have no stones on ultrasound and 33% have stones identified on ultrasonography. Maximum number of acute pancreatitis found in age group 21y-30y 24.5%. Conclusion: In our study 35(33%) found to have acute pancreatitis secondary to gall stones, 68(64.2%) found to have no stones. Females outnumbered in all age groups. Keywords: Acute pancreatitis, gall stones, CT severity index, prevalence, LRH MTI.